Membrane electrode composite fiber titanium felt structure and preparation method thereof
Patent Information
- Application Number
- CN202410068325.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-17
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-01-17
AI Technical Summary
[0004]针对现有技术中的技术问题,本发明的目的在于提供一种膜电极复合纤维钛毡结构,解决了钛纤维丝会侵入膜电极,热压时钛纤维丝会扎破膜电极的问题
[0022] 1. This invention provides a composite fiber titanium felt structure that can effectively protect the membrane electrode from intrusion and damage, with low cost and strong practicality. Specifically, it employs a method of spreading one or more layers of drawn titanium fibers on a titanium felt matrix, such as a titanium felt matrix prepared from diced titanium fibers. Due to the good flexibility of drawn titanium fibers, covering the surface of the titanium felt with them can protect the membrane electrode, effectively solving the problems of titanium fiber intrusion into the membrane electrode and titanium fiber puncture of the membrane electrode during hot pressing. At the same time, drawn titanium fibers also have a large specific surface area, which can ensure the pore structure and improve the mass transfer capacity of the titanium felt. When used in membrane electrodes, it can improve the efficiency of the electrolyzer and better meet the usage requirements of the electrolyzer.
Smart Images

Figure CN117867549B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of membrane electrode structure technology, specifically to a membrane electrode composite fiber titanium felt structure and its preparation method. Background Technology
[0002] Titanium felt, also known as titanium fiber felt or titanium fiber diffusion layer, is a three-dimensional mesh structure material woven from titanium metal fibers. It has excellent intercrystalline and capillary pore structures and is often used as one of the core components of PEM water electrolysis membrane electrodes. It is used as a carrier for gas-liquid transport and has excellent corrosion resistance, gas-liquid mass transfer capability, and electrochemical performance.
[0003] Currently, titanium felt is typically made from diced titanium fibers, becoming diced titanium fiber felt. Diced titanium fibers are titanium filaments obtained through a cutting method. The cutting method is highly efficient and low-cost, and is widely used in the preparation of titanium fiber felt. Studies have shown that the pore structure of titanium felt has a significant impact on membrane electrode performance; excessively coarse or fine pores will reduce gas-liquid transport efficiency. However, due to the manufacturing characteristics of diced titanium fiber felt, pore inhomogeneity is unavoidable. Furthermore, during membrane electrode use, some areas of the diced titanium fiber felt have larger surface pores, causing the diced titanium fiber filaments to intrude into the membrane electrode, thus affecting the performance of the PEM electrolyzer. During the hot pressing process in membrane electrode preparation, these titanium fiber filaments may also puncture the perfluorosulfonic acid membrane, damaging the membrane electrode structure and rendering the membrane electrode unusable. Summary of the Invention
[0004] To address the technical problems in existing technologies, the present invention aims to provide a membrane electrode composite fiber titanium felt structure, which solves the problems of titanium fiber filaments intruding into the membrane electrode and puncturing the membrane electrode during hot pressing. The present invention also provides its preparation method.
[0005] To achieve the above objectives, the technical solution provided by this invention is as follows:
[0006] On one hand, the present invention provides a membrane electrode composite fiber titanium felt structure, including a titanium felt matrix and a protective fiber layer, wherein the protective fiber layer covers the outer surface of the titanium felt matrix, and the protective fiber layer includes at least one layer of drawn titanium fiber.
[0007] This invention provides a composite fiber titanium felt structure that effectively protects the membrane electrode from intrusion and damage, with low cost and strong practicality. Specifically, it involves attaching one or more layers of drawn titanium fibers to a titanium felt matrix, such as one prepared from machined titanium fibers. Due to the good flexibility of the drawn titanium fibers, covering the surface of the titanium felt can protect the membrane electrode, effectively solving the problems of titanium fiber intrusion into the membrane electrode and titanium fiber puncture of the membrane electrode during hot pressing. At the same time, the drawn titanium fibers also have a large specific surface area, which can ensure the pore structure and improve the mass transfer capacity of the titanium felt. When used in membrane electrodes, it can improve the efficiency of the electrolyzer and better meet the usage requirements of the electrolyzer.
[0008] Because drawn titanium fibers can increase the contact area between the titanium felt structure and the membrane electrode, thereby reducing the ohmic resistance of the PEM electrolyzer, and because drawn titanium fibers do not penetrate into the membrane electrode, they also protect it. Furthermore, using one or more layers of drawn titanium fibers, compared to using drawn titanium fibers for the entire titanium felt structure, can significantly reduce the cost of the titanium felt and broaden its application range.
[0009] Furthermore, the existing method of spraying metal particles can be improved. In this method, the metal particles cover the pores of the titanium felt substrate, reducing the pore size. Moreover, due to uneven metal particle coverage, some pores may be blocked, hindering gas-water transport and increasing mass transfer resistance, leading to reduced performance of the membrane electrode in high current density regions. The composite fiber titanium felt structure described in this application effectively avoids these problems. It not only has a better pore structure, but more preferably, it can achieve a gradient pore structure, effectively solving the problem of titanium fiber filaments intruding into the membrane electrode or puncturing the membrane, resulting in good applicability.
[0010] Based on the above technical solution, the protective fiber layer includes multiple layers of drawn titanium fibers, and a gradient pore structure is formed sequentially between the titanium felt matrix and the multiple layers of drawn titanium fibers. The surface porosity of the drawn titanium fibers is 40%-60%; preferably, the surface pores of the drawn titanium fibers are 5-10 μm.
[0011] Based on the above technical solution, the diameter of the drawn titanium fiber is 0.008-1mm and the length is 3-20mm.
[0012] The thickness of the protective fiber layer is sprayed according to actual needs, i.e., the number of layers of drawn fibers and the thickness of each layer are designed accordingly, as long as the surface of the cut titanium fiber felt is completely covered. Preferably, a single layer of drawn titanium fibers is provided on the outer surface of the titanium felt substrate. Different sizes of drawn titanium fibers can be used. Depending on the applicable diameter and length of drawn titanium fibers, different gap sizes can be obtained, making the gap controllable to meet the requirements of electrolytic cells for different pore sizes, thus enhancing applicability. Preferably, multiple layers of drawn titanium fibers are disposed on the outer surface of the titanium felt substrate, forming a gradient porosity structure. This can be achieved by plasma spraying, sequentially applying dried, large-sized drawn titanium fibers to the outer surface of the cut titanium fiber felt substrate, followed by applying dried, small-sized drawn titanium fibers to the outer surface of the large-sized drawn titanium fiber layer. This gradient porosity design not only mitigates the negative impact of external impurities intruding into the titanium fiber felt but also achieves a gradient pore size, resulting in a pore diameter of 5-10 μm on the surface of the drawn titanium fibers. This improves the mass transfer capacity of the titanium fiber felt, increases the contact surface area, expands the three-phase interface for reaction, enhances the efficiency of the electrolyzer, and better meets the requirements of the electrolyzer. The drawn titanium fibers are prepared using a bundled drawing method.
[0013] Based on the above technical solution, the titanium felt matrix is made of cut titanium fiber felt; the thickness of the cut titanium fiber felt is 250-800μm, the porosity is 40%-60%, and the diameter of the titanium fiber is 30-50μm.
[0014] Preferably, the thickness of the cut titanium fiber felt is 250μm, 400μm or 800μm, the porosity is 40%, 50% or 60%, and the diameter of the titanium fiber is 30μm, 40μm or 50μm.
[0015] On the other hand, the present invention provides a method for preparing a membrane electrode composite fiber titanium felt structure, comprising the following steps:
[0016] Step 1: Dry the drawn titanium fibers to be used and set aside.
[0017] Step 2: Lay the drawn titanium fibers obtained in Step 1 on the titanium felt matrix, and then sinter them to fix the drawn titanium fibers and the cut titanium fiber felt.
[0018] Step 3: After cooling, the final membrane electrode composite fiber titanium felt structure is obtained.
[0019] Based on the above technical solution, the sintering conditions for the drawn titanium fiber and the cut titanium fiber felt in step two are: sintering at a temperature of 400-500℃ for 1 hour.
[0020] The membrane electrode conforming to the fiber titanium felt structure is prepared by sintering. The preparation method is simple and easier to operate than the ion spraying method commonly used in the prior art. It is also lower in cost and has good applicability.
[0021] The beneficial effects of the technical solution provided by this invention are as follows:
[0022] 1. This invention provides a composite fiber titanium felt structure that can effectively protect the membrane electrode from intrusion and damage, with low cost and strong practicality. Specifically, it employs a method of spreading one or more layers of drawn titanium fibers on a titanium felt matrix, such as a titanium felt matrix prepared from diced titanium fibers. Due to the good flexibility of drawn titanium fibers, covering the surface of the titanium felt with them can protect the membrane electrode, effectively solving the problems of titanium fiber intrusion into the membrane electrode and titanium fiber puncture of the membrane electrode during hot pressing. At the same time, drawn titanium fibers also have a large specific surface area, which can ensure the pore structure and improve the mass transfer capacity of the titanium felt. When used in membrane electrodes, it can improve the efficiency of the electrolyzer and better meet the usage requirements of the electrolyzer.
[0023] 2. This application also provides a method for preparing composite fiber titanium felt structure, which adopts a sintering process. The preparation method is simple and easy to operate. Compared with the ion spraying method commonly used in the prior art to prepare coatings, the method is simpler and easier to operate, lower in cost, and more practical. Attached Figure Description
[0024] Figure 1 This is a schematic diagram of the structure of Embodiment 1 of the present invention;
[0025] Figure 2 This is a schematic diagram of the structure of Embodiment 2 of the present invention;
[0026] Figure 3 This is a schematic diagram of the structure of Embodiment 3 of the present invention; Detailed Implementation
[0027] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0028] Unless otherwise defined, all technical and scientific terms used in this specification have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to limit the invention. The term "and / or" as used in this specification includes any and all combinations of one or more of the associated listed items. It should be understood that, unless otherwise specified, all the various materials used in this invention are commercially available.
[0029] Example 1
[0030] like Figure 1 As shown, a membrane electrode composite fiber titanium felt structure in this embodiment includes a titanium felt substrate and a protective fiber layer. The protective fiber layer covers the outer surface of the titanium felt substrate and includes a single layer of drawn titanium fibers. The titanium felt substrate is made of cut titanium fiber felt with a thickness of 0.25 mm, a porosity of 50%, and a diameter of 50 μm. The drawn titanium fibers have a diameter of 50 μm and a length of 3 mm.
[0031] This invention provides a method for preparing a membrane electrode composite fiber titanium felt structure, comprising the following steps:
[0032] Step 1: Dry the required drawn titanium fibers and set them aside.
[0033] Step 2: Lay 50μm diameter and 3mm length drawn titanium fibers on the cut titanium fiber felt and sinter them in a high-temperature furnace at 500℃ for 1 hour.
[0034] Step 3: Take out the sintered titanium fiber felt and let it stand at room temperature to obtain a composite fiber titanium felt structure with a surface porosity of 40%.
[0035] In this embodiment, a composite fiber titanium felt structure with a single layer of drawn titanium fibers, formed by sintering, is used to protect the membrane electrode and solves the problems of titanium fiber filaments intruding into the membrane electrode and puncturing the membrane electrode during hot pressing.
[0036] Example 2
[0037] like Figure 2 As shown in this embodiment, a membrane electrode composite fiber titanium felt structure includes a titanium felt substrate and a protective fiber layer. The protective fiber layer covers the outer surface of the titanium felt substrate and comprises multiple layers of drawn titanium fibers, forming a gradient pore structure. The titanium felt substrate is a cut titanium fiber felt with a thickness of 0.4 mm, a porosity of 50%, and a diameter of 50 μm. The drawn titanium fibers are of two types: one with a diameter of 100 μm and a length of 5 mm, and the other with a diameter of 50 μm and a length of 3 mm.
[0038] This invention provides a method for preparing a membrane electrode composite fiber titanium felt structure, comprising the following steps:
[0039] Step 1: Dry the required drawn titanium fibers and set them aside.
[0040] Step 2: Lay drawn titanium fibers with a diameter of 100μm and a length of 5mm on the cut titanium fiber felt; place it in a high-temperature furnace for sintering at a temperature of 500℃ for 1 hour;
[0041] Step 4: Take out the sintered titanium fiber felt and let it reach room temperature; lay 50μm diameter and 3mm length drawn titanium fibers on the cut titanium fiber felt; put it into a high temperature furnace for sintering at 500℃ for 1 hour.
[0042] Step 5: Take out the sintered titanium fiber felt and let it stand at room temperature to obtain a composite fiber titanium felt structure with a surface porosity of 40%.
[0043] In this embodiment, a composite fiber titanium felt structure with multiple layers of drawn titanium fibers, formed by sintering, is used. This not only solves the problems of titanium fiber filaments intruding into the membrane electrode and puncturing the membrane electrode during hot pressing, but also has a gradient pore structure, which improves the mass transfer capacity of the titanium fiber felt, increases the contact surface area, increases the three-phase interface where the reaction occurs, and improves the utilization efficiency of the electrolytic cell.
[0044] Example 3
[0045] like Figure 3 As shown, a membrane electrode composite fiber titanium felt structure in this embodiment includes a titanium felt substrate and a protective fiber layer. The protective fiber layer covers the outer surface of the titanium felt substrate and includes a single layer of drawn titanium fibers. The titanium felt substrate is made of cut titanium fiber felt with a thickness of 0.25 mm, a porosity of 50%, and a diameter of 50 μm. The drawn titanium fibers have a diameter of 100 μm and a length of 5 mm.
[0046] This invention provides a method for preparing a membrane electrode composite fiber titanium felt structure, comprising the following steps:
[0047] Step 1: Dry the required drawn titanium fibers and set them aside.
[0048] Step 2: Lay drawn titanium fibers with a diameter of 100μm and a length of 5mm on the cut titanium fiber felt; place it in a high-temperature furnace for sintering at a temperature of 500℃ for 1 hour;
[0049] Step 3: Take out the sintered titanium fiber felt and let it stand at room temperature to obtain a composite fiber titanium felt structure with a surface porosity of 60%.
[0050] This embodiment employs a composite fiber titanium felt structure, formed by sintering a single layer of drawn titanium fibers, which protects the membrane electrode and solves the problems of titanium fiber filaments intruding into the membrane electrode and puncturing the membrane electrode during hot pressing. Unlike Embodiment 1, this embodiment uses larger drawn titanium fibers, resulting in greater porosity on the surface of the drawn titanium fiber layer after spraying. When designing the titanium felt porosity, the size of the coating gap can be changed by controlling the dimensions of the drawn titanium felt, achieving controllable gaps to meet the different porosity requirements of the electrolytic cell.
[0051] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered illustrative and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.
[0052] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A membrane electrode composite fiber titanium felt structure, characterized in that, The device comprises a titanium felt matrix and a protective fiber layer, wherein the protective fiber layer covers the outer surface of the titanium felt matrix and includes at least one layer of drawn titanium fibers; the surface porosity of the drawn titanium fibers is 40%-60%, the diameter of the drawn titanium fibers is 0.008-1 mm, and the length is 3-20 mm; the titanium felt matrix is made of cut titanium fiber felt; the thickness of the cut titanium fiber felt is 250-800 μm, the porosity is 40%-60%, and the diameter of the titanium fibers is 30-50 μm.
2. The membrane electrode composite fiber titanium felt structure according to claim 1, characterized in that, The protective fiber layer comprises multiple layers of drawn titanium fibers, and a gradient pore structure is sequentially formed between the titanium felt matrix and the multiple layers of drawn titanium fibers.
3. A method for preparing a membrane electrode composite fiber titanium felt structure according to any one of claims 1 or 2, characterized in that, Includes the following steps: Step 1: Dry the drawn titanium fibers to be used and set aside. Step 2: Lay the drawn titanium fibers obtained in Step 1 on the titanium felt matrix, and then sinter them to fix the drawn titanium fibers and the cut titanium fiber felt. Step 3: After cooling, the final membrane electrode composite fiber titanium felt structure is obtained.
4. The method for preparing a membrane electrode composite fiber titanium felt structure according to claim 3, characterized in that, The sintering conditions for the drawn titanium fiber and the cut titanium fiber felt in step two are: sintering at a temperature of 400-500℃ for 1 hour.
Citation Information
Patent Citations
High-purity high-strength titanium fiber felt and preparation method thereof
CN115418663A
Metal fiber and preparation method thereof
CN116475262A